Senses of Scripture in the Second Century: Irenaeus, Scripture, and Noncanonical Christian Texts. - Bingham, D. Jeffrey (Journal of Religion, 2017)
The article focuses on the Christian scriptures of the second and fourth century and discusses the concept of these scriptures by analyzing the writings of Bishop Irenaeus. Topics discussed include the Bible, the definitions of terms canons and scriptures, and Irenaeus's notion of scriptures. Also mentioned are several books by Bishop Papias.